Fatigue and quality of sleep jointly influence the association between physical activity and health-related quality of life in patients with chronic kidney disease: a cross-sectional study - De Gucht, Véronique; Woestenburg, Dion H. A.; Pizzulin, Vesna Vrecko; Cromm, Krister (Frontiers in Nephrology, 2025)
IntroductionFatigue is a prevalent and burdensome symptom in Chronic Kidney Disease (CKD), with major impact on Health-Related Quality of Life (HRQoL). Physical activity has been linked to improvements in both fatigue and HRQoL. This study examined whether physical activity relates to HRQoL indirectly through fatigue and whether this relationship is moderated by sleep quality.MethodsA total of 465 CKD patients (mean age = 53.78 years; 50% female) participated in the study. Fatigue, physical activity, HRQoL, and sleep quality were assessed and compared to general population norms and across treatment modalities using t-tests and ANCOVAs. Mediation, moderation, and moderated mediation analyses were conducted.ResultsCKD patients reported lower physical activity levels, HRQoL, and sleep quality, and higher fatigue than the general population (all ps <.001). Among treatment groups, transplant recipients showed the most favorable outcomes, while patients without renal replacement therapy reported the poorest. Higher levels of physical activity were associated with better HRQoL indirectly through fatigue, with small to moderate effect sizes. Stronger associations observed in those reporting better sleep quality.DiscussionThese findings indicate that physical activity is associated with better HRQoL in CKD patients through its relationship with fatigue, particularly among those with good sleep quality. Future research should explore fatigue across CKD stages to optimize interventions that target both physical activity and sleep.